Transformative Trends and Future Directions in Digital Language Services: Innovations, Challenges, and Competitive Strategies in the Globalized Information Age - Kang, Xing (Forum for Linguistic Studies, 2025)
Digital language services (DLS) are playing an increasingly important role in the rapid development of globalized information technologies. The objective of this study is to explore the transformative trends and future directions in DLS including innovations, challenges, and competitive strategies in the information age. Through a qualitative review method, i.e., an in-depth exploration of social phenomena, inner properties of issues, and paradoxical changes in research, this study concludes that DLS providers, looking into the future, should keep open-minded and positive attitudes toward the development of DLS. Future development of DLS will be characterized by the multiple trends toward intelligent, automatic, balancing globalization and localization, multimodal and cross-media, data security, privacy protection, talent cultivating, and team building. These trends will promote the continuous innovation and development of DLS industries, providing highly efficient, accurate, tailored, and personalized language services. To address future challenges and meet future benefits, DLS providers should pay close attention to marketing dynamism and technological innovations, enhance technological revolution, cultivate DLS talents, and improve the quality and competitiveness of DLS to meet the increasingly intense marketing competition. Future research directions will focus on technological innovation and integration, innovation of service models, construction of human ethics and norms, expansion of the application market, and improvement in service quality